Cutaneous reactive B‐cell lymphoid proliferations. (4th August 2022) - Khalil, Shadi; Donthi, Deepak; Gru, Alejandro A.
Abstract: Cutaneous lymphoid hyperplasia (CLH), also known as cutaneous pseudolymphoma, is a spectrum of benign conditions characterized by reactive B‐ and T‐cell cutaneous lymphocytic infiltrates. B‐cell lymphoid proliferations are a heterogenous group of non‐neoplastic cutaneous diseases that must be histopathologically distinguished from cutaneous B‐cell lymphomas. These proliferations can be observed as reactive phenomena to infections, medications, allergens, neoplasms, and more. Furthermore, there are many inflammatory conditions that present with reactive B‐cell infiltrates, including actinic prurigo, Zoon balanitis, Rosai‐Dorfman disease, and cutaneous plasmacytosis. This review summarizes multiple cutaneous B‐cell lymphoid proliferations within the major categories of reactive and disease‐associated CLH. Further we discuss major discriminating features of atypical CLH and malignancy. Understanding the specific patterns of B‐cell CLH is essential for the proper diagnosis and treatment of patients presenting with such lesions.